Quantifying Research Productivity: A Bibliometric Analysis of Ethnoscience - Syahida Ainaya; Winny Liliawati; Lilit Rusyati (Universitas Negeri Yogyakarta, 2026)
This study aims to investigate the progress of ethnoscience research published on Google Scholar between 1966 and 2023, utilizing a computational bibliometric analysis approach with the assistance of the Publish or Perish and VOSviewer applications. Parameters including title, publication type, keywords, Citation, and year range were utilized to select the relevant data obtained from the Publish or Perish applications, resulting in a compilation of 252 articles related to the chosen theme, each spanning a period of 10 years, starting from theory, society, culture, and education, up to chemistry and physic subjects, supported by highly cited journal findings. The trending topics in the field of education are approaches and learning media. Based on the gathered data, it is evident that there are still numerous opportunities for further research in the field of Ethnoscience. The utilization of the VOSviewer application can aid in identifying problematic areas that can be explored as potential research innovation topics within the field of ethnoscience. Future research should explore the integration of ethnoscience with sustainability, digital learning, and global challenges while addressing gaps in knowledge and underrepresented contexts.